IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT SIKAP DAN PERILAKU POSITIF SISWA DI SMP INSAN GEMILANG BLORA KABUPATEN BLORA - FARID NUR ROHMAN; MANSUR; AGUS KURNIAWAN (UNISAN JURNAL, 2024)
This study aims to describe the implementation of character education. This study uses a qualitative approach with a descriptive method. Therefore, this research is a qualitative descriptive study. Research data were collected through observation, interviews, and documentaries. And for data that looks bright, categorization is made with a coding system. The validity of the data is done through the triangulation method. Data were analyzed during and after the study. The results of the study indicate that the implementation of character education in SMP Insan Gemilang Blora Kabupaten Blora has the main competencies that are mastered by each teacher, namely; RPP regulates competence, curriculum implementation and evaluation. So, the implementation of character education in each lesson is through: making graduate competency standards (SKL) which are prepared by standards (SK), learning indicators are arranged, learning evaluation strategies apply all of these improvements with supporting factors and limiting factors. Big meaning, has research implications, namely every teacher must have professionalism, good workers, fresh functions, and credible performance. That is, having the implementation of character education is education with aspects of building morals, (ethics-aesthetics), cognitive, feelings, and psychomotor actions. Keywords: Management , Character Education, Interests, Positive Attitudes and Behaviors